Application and nursing of prone ventilation technique in ICU (俯卧位通气技术在ICU的应用及护理) - DAI Hongran (代洪然); WANG Huazhi (王华枝); LI Yuhua (李玉华); MA Haihong (马海红) (中西医结合护理)
Objective To explore the therapeutic effect and nursing experience of patients with respiratory failure in ICU after prone ventilation. Methods From January 2020 to January 2021, 4 patients with acute respiratory distress syndrome (ARDS) and 1 patient with atelectasis admitted to the Intensive Care Unit were retrospectively analyzed. The effect of prone ventilation was studied, and the nursing experience was summarized. Results After the treatment with prone ventilation, the blood oxygen saturation of 4 patients increased from 85%～93% to 95%～99%, and the sputum was effectively aspirated. CT examination of 1 patient with atelectasis showed significant improvement in lung inflammation. Conclusion The application of prone ventilation in patients with ARDS and atelectasis in ICU can significantly improve the pulmonary ventilation function, promote the effective discharge of pulmonary secretions, increase the functional residual capacity, thus improve the cardiorespiratory fitness and promoting the recovery of patients. (目的 探讨ICU呼吸衰竭患者进行俯卧位通气后的治疗效果及护理经验。方法 回顾性分析2020年1月—2021年1月收治的采用俯卧位通气治疗的急性呼吸窘迫综合征(ARDS)4例和肺不张患者1例的临床资料, 总结护理经验。结果 经俯卧位通气治疗, 本组患者血氧饱和度明显提高, 痰液有效排出, 痰液性质改善, 其中肺不张患者的肺部炎症明显好转。结论 俯卧位通气干预联合专业护理能明显改善患者肺部通气功能, 促进肺部分泌物有效排出, 增加功能残气量, 从而减轻心肺负荷, 有利于疾病恢复。)